2017
DOI: 10.1167/iovs.17-21593
|View full text |Cite
|
Sign up to set email alerts
|

The Urokinase Receptor-Derived Peptide UPARANT Recovers Dysfunctional Electroretinogram and Blood–Retinal Barrier Leakage in a Rat Model of Diabetes

Abstract: These data suggest that targeting the urokinase-type plasminogen activator and its receptor system by systemic UPARANT is a potential therapeutic approach for the treatment of early diabetic retinopathy, thus providing a potential alternative approach to delay disease progression in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 54 publications
16
34
0
Order By: Relevance
“…UPARANT was cleared from the plasma with a t 1/2 of 2.2 hours in the elimination phase. Control values were in line with a previous work . No differences were found between control and STZ rats.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…UPARANT was cleared from the plasma with a t 1/2 of 2.2 hours in the elimination phase. Control values were in line with a previous work . No differences were found between control and STZ rats.…”
Section: Resultssupporting
confidence: 92%
“…In all experiments, no differences were observed between untreated and vehicle‐treated rats. UPARANT dose and regimen were in line with those used in previous studies . The rats were kept individually in metabolic cages for 24 hours to collect urine for the measurement of urine output.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown by additional findings, UPARANT can be detected in the eye 2 hours after its administration and its delivery to the retina is approximately 15% of that in the eye indicating its ability to cross the BRB and supporting the validity of subcutaneous administration as potentially effective in the treatment of ocular diseases. After 24 hours, UPARANT level in the eye is about 20% of that at 2 hours indicating a half‐life of approximately 10‐11 hours and suggesting a potential long duration of the intraocular pharmacologic effect . UPARANT dose and regimen used here are in line with those used in previous studies in rats in which systemic treatment with the drug was shown both effective and safe …”
Section: Discussionsupporting
confidence: 83%